Massive Health Record Breaches Evidenced by the Office for Civil Rights Data - Waldemar W. KOCZKODAJ; Jolanta MASIAK; Mirosław MAZUREK; Dominik STRZAŁKA; Pavel F. ZABRODSKII (Tehran University of Medical Sciences, 2019)
Background: Using data collected by the Office for Civil Rights, Department of Health and Human Services (HHS), over half of the population in the USA might have been affected by security breaches since Oct 2009. This study provided analysis of the data, presenting the numbers of individuals affected in one breach and the number of breaches. Methods: Statistical analysis has been conducted with visualizations. Visualizations include categorized histograms and tables. Histograms are presented as bar charts with categories: location and breach type. Tables show case counts (across top 10 breaches and those with more than one million stolen records) in successive years and covered entity types. All statistics were calculated with the use of package R. Analyzed data were collected from Oct 2009 till Jun 2017. Results: This study presents evidence of health data breaches taking place at an unprecedented level. Medical records of at least 173 million of people, gathered since Oct 2009, have been breached and might have adversely influenced over half of the population in the USA. Conclusion: Results of this study are expected to motivate public care authorities to develop similar laws and regulations as the USA while striving for better law enforcement. It takes a considerable amount of time to educate public and it takes substantial financial resources to prevent data breaches.